Improved gellan gum production by a newly-isolated Sphingomonas azotifigens GL-1 in a cheese whey and molasses based medium. (August 2020) - Wang, Dexin; Kim, Hyangmi; Lee, Sungbeom; Kim, Dae-Hyuk; Joe, Min-Ho
Graphical abstract: Highlights: A novel strain producing gellan gum was isolated and identified as S . azotifigens. The media for gellan gum production were optimized using cheese whey and molasses. A maximum gellan gum of 33.75 g/L was produced in cheese whey based medium. Provide a strategy for gellan gum production by industrial by-products. Abstract: Gellan gum is a water-soluble exopolysaccharide, it has applications in the food, pharmaceutical and chemical industries. In this study, a gellan gum producing strain was isolated from rice root, and this strain was identified be the species of Sphingomonas azotifigens . The Plackett-Burman design was applied to investigate the main factors affecting gellan gum production by S. azotifigens GL-1 in a molasses and cheese whey based medium; the medium compositions were optimized by response surface methodology. The optimum cheese whey based medium consisted of cheese whey 68.34 g/L, Na2 HPO4 14.58 g/L and KH2 PO4 7.66 g/L, and the maximum gellan gum production that using this medium was 33.75 ± 1.55 g/L. 14.75 ± 0.65 g/L gellan gum was obtained with an optimized molasses medium, which consisted of molasses 50 g/L, Na2 HPO4 9.71 g/L and KH2 PO4 5.92 g/L. The molecular weight of gellan gum obtained from two medias were 1.06 × 10 6 and 0.89 × 10 6 Da, respectively. The cheese whey-derived gellan gum showed a higher rhamnose, lower glucuronic acid and higher glycerate content compared to the molasses-derived gellan gum. S. azotifigens GL-1 has a high gellan gum production capacity in a cheap medium suggesting it has great potential as an industrial gellan gum producer.